The different effect of consumer learning on incentives to differentiate in Cournot and Bertrand competition - Maximilian Conze; Michael Kramm (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
We combine two extensions of the differentiated duopoly model of Dixit (1979), namely Caminal and Vives (1996) and Brander and Spencer (2015a,b), to analyze the effect of consumer learning on firms' incentives to differentiate their products in models of Cournot and Bertrand competition. Products are of different quality, consumers buy sequentially and are imperfectly informed about the quality of the goods. Before simultaneously competing in quantities, firms simultaneously choose their investment into differentiation. Late consumers can observe earlier consumers' decisions and extract information about the quality of the goods. This influences the firms' incentives to differentiate. If firms compete in quantities, they are more likely to invest in differentiation with consumer learning than without. This is in line with implications of the recommendation effect introduced in Conze and Kramm (2016) in a model of spatial differentiation. We also examine the case in which firms compete in prices. Here, the effect of consumer learning is reversed, so that differentiation is less likely with consumer learning. Thus, we find an information-based difference between Cournot and Bertrand competition: in the Bertrand setting consumer learning increases the competition, i.e. products are more likely to be substitutes, and it weakens it in the Cournot model. – – Wir kombinieren zwei Erweiterungen des Duopol Models mit differenzierten Gütern von Dixit (1979), genauer die von Caminal und Vives (1996) und die von Brander und Spence (2015a,b), um den Effekt von (Bayesianisch) lernenden Konsumenten auf Anreize der Firmen zur Produktdifferenzierung im Cournot und im Bertrand Wettbewerb zu analysieren. Die Produkte haben eine unterschiedliche Qualität, Konsumenten kaufen sequentiell und sind unvollständig über die Produktqualität informiert. Bevor die Firmen simultan über ihre produzierten Mengen entscheiden, wählen sie simultan ihre Investitionen in Produktdifferenzierung. "Spätere" Konsumenten können die Konsumentscheidungen "früherer" Konsumenten beobachten und so Information über die Produktqualität erhalten, also Bayesianisch lernen. Im Cournot Wettbewerb mit lernenden Konsumenten ist es wahrscheinlicher, dass Firmen in Produktdifferenzierung investieren, als ohne. Dieses Ergebnis stimmt überein mit dem Wirken des "Recommendation Effects", welcher in Conze und Kramm (2016a) gezeigt und analysiert wird. Wir untersuchen auch den Bertrand Wettbewerb. Hier ist der Effekt von Konsumentenlernen umgekehrt, so dass Differenzierung mit Konsumentenlernen weniger wahrscheinlich ist also ohne. Wir finden demnach einen informationsbasierten Unterschied zwischen Cournot und Bertrand Wettbewerb: im Bertrand Modell erhöht Konsumentenlernen den Wettbewerb, das heißt Produkte sind mit lernenden Konsumenten eher Substitute als ohne, und im Cournot Modell schwächt es ihn ab.
Keywords: L13; L15; D83; 330; principle of minimum differentiation; consumer learning; Bayesian observational learning